Numerical simulations of the wing wake and tip vortex for air-to-air refuelling - Miranda, Alice (Cranfield University, 2012)
The present research was carried out in the framework of the ASTRAEA II project, in collaboration with Cobham Mission Equipment. One part of the overall ASTRAEA II project is to design an autonomous air-refuelling system based on a wake model computed in real-time, which allows the flow field to be visualised in a Synthetic Environment. In a previous part of the ASTRAEA project a MATLAB® code was developed based on the extended lifting line method (referred to as the ELL code) which provides a refuelling tanker wake model. The aim of this project is to understand the tanker wake, to provide more detailed flow field predictions and to compare the results with the results from the ELL code to validate this reduced fidelity method. The understanding of the tanker wake and tip vortices was carried out through the use of computational fluid dynamics (CFD) methods. CFD simulations of three geometries were carried out and post-processed: the DLR- F6 aircraft geometry, the CRM aircraft geometry (both similar to the A330) and the NACA0015 swept wing model of Gerontakos and Lee. The latter was used as a validation test case for the CFD modelling of the wake and the tip vortex. The CFD simulations were performed using a geometry definition compatible with the idealised model scale aircraft definitions used in the wind tunnel experiments. Finally comparisons between the available CFD results and the ELL code were carried out. The ELL code computes a qualitatively similar wake and tip vortex flow field, but only when the code is run with a different set-up which requires more computing resources. The addition of the simple fuselage model to the ELL code has provided an improvement in the results compared with the CFD solutions. The ELL code does not model the vortex roll up and there are notable differences in the near-field region in particular. Although the flow field structure is similar between the ELL and the CFD results, there are notable differences in the local disturbance flow field. In particular, for some configurations, the tip vortex strength is underpredicted by up to a factor of three relative to the CFD results.